A financial decision support framework for the appraisal of renewable energy infrastructures in developing economies. Issue 2 (1st June 2015) - Kozlovski, Eugene; Bawah, Umar
Abstract : Purpose: – The paper aims to report on an integrated techno-economic framework for the performance analysis of energy production based on the renewable energy resources (RERs). Whilst the majority of existing studies have focussed on technical aspects of RER modelling, the proposed framework incorporates financial assessment into the process of appraising the alternatives of hydropower, wind energy and solar energy infrastructures. An approach to the optimal choice of RER deployment for a specific developing region is formulated and applied to Ghana. Design/methodology/approach: – A model comprising technical and economic parameters was developed for analysing the investment rankings of different RERs and comparing them to that of conventional energy sources such as the natural gas combined cycle (NGCC) electric plant. The analysis also included the carbon cost and power generation capacity. The total life cycle costing and levelised cost of energy generated from each resource were modelled for three corporate ownership structures: a public utility that is not tax-liable (no-tax case); organisational power generation for internal use, ultimately concerned with its after-tax costs (after-tax case); and an independent power producer for the market, with before-tax revenues covering all costs (before-tax case). Findings: – Using the empirical data from Ghana together with the proposed framework, it is shown that when carbon incentives are provided, the hydroelectric and wind conversion infrastructures can effectively compete with the conventional NGCC in this country, whilst with no carbon credit, NGCC still appears to be the most viable option. Practical implications: – Policy-related recommendations on carbon incentives and preferential power purchase prices, which are critical for widespread RER deployment, can be directly derived from this research. Originality/value: – The study represents a comprehensive decision-making tool that can be used in regulatory and investment analysis on the expansion of RER systems in the developing countries.